(untitled) (Nexo Revista Científica, 2021)
A heat exchanger is any device in which energy is transferred in the form of heat. In the present work, the thermal-hydraulic rating of a proposed shell and tube heat exchanger was carried out to accomplish the heating of an acetone stream from 25 to 60 ºC, using hot water at 90 ºC as heating agent. The suggested equipment can be used satisfactorily to perform the required heat transfer service since the calculated percent excess area does not exceed 40%, and the pressure drop values for both streams do not exceed the maximum limits established by the process. The proposed heat exchanger is feasible to use for a range of the acetone feed flow rate of 15.15 - 28.70 kg/s, and for a range of the acetone inlet temperature of 7.95 – 32.60 ° C.